Low-foam low-main-salt type acidic electroplating zinc-nickel alloy additive and electroplating solution
Patent Information
- Application Number
- CN202610850542.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-12
- Publication Date
- 2026-09-18
AI Technical Summary
[0005]消泡剂的使用不当会对镀层造成负面影响;如过量消泡剂可能在镀液表面形成薄膜,影响工件润湿性,导致镀层出现漏镀或条纹;低质量消泡剂可能含有杂质(如硅酮类),在镀液中积累后易吸附于镀层,引发针孔或结合力下降;可能干扰光亮剂、整平剂的功能,影响镀层光泽或均匀性
本发明的添加剂中,首次使用了萘酚烷氧基化合物作为基础细化剂,使用该添加剂制备的电解液,在锌离子浓度为10-20g/L、镍离子浓度为5-15g/L的情况下,仍可得到镀层结晶细致,厚度、镍含量正常(10-16%)的锌镍镀层,有效降低了生产成本和带出消耗,且该电镀液泡沫少、易于管理。
Smart Images

Figure CN122773440A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of acidic zinc plating and zinc alloy electroplating solutions, specifically to a low-foaming, low-primary-salt acidic zinc-nickel alloy electroplating additive and electroplating solution. Background Technology
[0002] With the development of industrial technology, the requirements for the protective performance of metal surfaces are getting higher and higher. Zinc-nickel alloy, as a protective coating, has become an ideal choice to replace traditional cadmium plating and pure zinc plating due to its excellent corrosion resistance, low hydrogen embrittlement, good weldability and machinability. It is widely used in industrial fields such as automobiles, motorcycles and daily hardware.
[0003] Currently, the mainstream zinc-nickel alloy electroplating solution on the market is mainly alkaline zinc-nickel alloy electroplating solution. Although alkaline zinc-nickel alloy electroplating solution has a long history of application and a wide range of applications, its inherent defects limit its application in certain fields. For example, the current efficiency of alkaline zinc-nickel alloy electroplating solution is extremely low (usually only 50%-60%), resulting in serious energy waste; during use, alkaline zinc-nickel alloy electroplating solution will continuously accumulate sodium carbonate and may produce highly toxic cyanide ions, causing the plating solution to age and degrade in performance, requiring frequent treatment and replacement; in addition, alkaline zinc-nickel alloy electroplating solution has poor adaptability to substrates and is difficult to directly plate on materials with high carbon content and loose structure, such as cast iron and powder metallurgy.
[0004] Acidic zinc-nickel alloy electroplating technology exhibits significant advantages over alkaline zinc-nickel alloy electroplating technology. Its current efficiency reaches up to 90%, greatly reducing energy consumption. Moreover, its system is stable and does not produce cyanide or sodium carbonate, reducing aging and pollution problems at the source, and lowering maintenance costs and wastewater treatment pressure. Most importantly, acidic zinc-nickel alloy electroplating solutions have extremely strong compatibility with substrates, and can directly obtain high-quality coatings with good adhesion on cast iron and powder metallurgy parts that are traditionally difficult to process.
[0005] Improper use of defoamers can have a negative impact on the coating. For example, excessive defoamers may form a thin film on the surface of the plating solution, affecting the wettability of the workpiece and causing incomplete plating or streaks in the coating. Low-quality defoamers may contain impurities (such as silicones), which are easily adsorbed onto the coating after accumulating in the plating solution, causing pinholes or reduced adhesion. They may also interfere with the function of brighteners and leveling agents, affecting the gloss or uniformity of the coating.
[0006] It is evident that providing an acidic zinc-nickel alloy electroplating additive and electrolyte with low ion concentration and independent of defoamers is of great significance to the industry. Summary of the Invention
[0007] In view of this, the present invention provides a low-foaming, low-primary-salt acidic zinc-nickel alloy electroplating additive and electroplating solution; the electroplating solution uses a novel basic refining agent, which can make the zinc ion concentration 10-20g / L and the nickel ion concentration 5-15g / L, so that a zinc-nickel plating layer with fine crystals, normal thickness and nickel content can be obtained, thereby reducing production costs, reducing carry-out consumption, reducing the difficulty of post-plating water treatment, and the foaming phenomenon is very light, eliminating the need for defoamers.
[0008] The technical solution of the present invention is as follows: An acidic zinc-nickel alloy additive, comprising a basic refining agent of 0.5-5 g / L, a brightener of 0.005-1 g / L, a complexing agent of 0.5-5 g / L, and a buffer of 40-70 g / L; The basic refining agent is a naphthol alkoxy compound with a structure as shown in Formula I or Formula II, as follows:
[0009] (I)
[0010] (II) Among them, R1 is one of H, Cl, Br, NH2, and COCH3; R2 is one of H, F, Cl, Br, NH2, SO3K, or COCH3; R3 is one of H, CH2SO3K, CH2CH2SO3K, and CH2CH2CH2SO3K.
[0011] Preferably, when the naphthol alkoxy compound is an alkoxy compound of α-naphthol, such as in Formula II, R2 is any one of H, F, Cl, Br, NH2, SO3K, and COCH3, and R3 is any one of H, CH2SO3K, CH2CH2SO3K, and CH2CH2CH2SO3K. When the naphthol alkoxy compound is an alkoxy compound of β-naphthol, such as in Formula I, R1 is any one of H, Cl, Br, NH2, and COCH3, and R3 is any one of H, CH2SO3K, CH2CH2SO3K, and CH2CH2CH2SO3K.
[0012] Preferably, the number of poly(ethylene oxide) blocks (EO) in the naphthol alkoxy compound is m, and the number of poly(propylene oxide) blocks (PO) is n, wherein 1≤m≤20, 1≤n≤15, and preferably, 1≤m≤15, 1≤n≤10.
[0013] Preferably, the method for synthesizing the above-mentioned naphthol alkoxy compound is as follows: polymerizing a naphthol derivative with ethylene oxide to obtain a first block copolymer; The molar ratio of naphthol derivatives to ethylene oxide is 1:0.5-20; The first block copolymer is then further polymerized with propylene oxide to obtain the naphthol alkoxy compound; The molar ratio of naphthol derivatives to propylene oxide is 1:0.5-12.
[0014] Preferably, the molar ratio of the naphthol derivative to ethylene oxide is 1:1-15; The molar ratio of the naphthol derivative to propylene oxide is 1:1-8.
[0015] Preferably, the method for synthesizing the above-mentioned naphthol alkoxy compound is as follows: S1, place the naphthol derivative and the base in a reaction vessel and mix them. Purge the reaction vessel with nitrogen, evacuate it, and then dehydrate it under vacuum. Continue to add ethylene oxide and stir until homogeneous at 14-17 rpm. S2, control the pressure inside the reactor to ≤0.4MPa, the stirring speed to 14-17 rpm, and the temperature to 100-120℃, so that the naphthol derivative and ethylene oxide can undergo a polymerization reaction for 1-5 hours to obtain the first block copolymer; S3, add propylene oxide into the reactor, control the pressure inside the reactor to ≤0.4MPa, the stirring speed to 14-17 rpm, and the temperature to 100-120℃, so that the first block copolymer and propylene oxide continue to polymerize. The reaction time is 1-5h, and crude naphthol alkoxy compound is obtained. S4. Neutralize the crude naphthol alkoxy compound by adding a neutralizing agent, then add an adsorbent, and obtain the naphthol alkoxy compound after vacuum dehydration and drying.
[0016] Both the neutralizing agent and the adsorbent are commercially available chemicals.
[0017] Preferably, in step S1, the base is 0.20-0.30% of the mass of the naphthol derivative; the base is sodium hydroxide and / or potassium hydroxide; the gas is purged with high-purity nitrogen four times; and the vacuum degree is -0.1 MPa during evacuation.
[0018] The basic refining agent used in this invention has good wettability, can effectively improve the brightness and leveling performance in the medium and low current density region, and can increase the turbidity point of the plating solution. Moreover, due to its low foaming properties, it does not affect the electroplating effect.
[0019] Preferably, the brightening agent is one or more of benzyl acetone, butynediol, butynediol monooxygenate, sodium vinyl sulfonate, and sodium saccharin.
[0020] Preferably, the complexing agent is any one or a combination of diethylenetriamine, hydroxyethyldiethylenetriamine, tetraethylenepentamine, triethanolamine, N,N-tetramethylethylenediamine, 1,1,4,7,10,10-hexamethyltriethylenetetramine, pentamethyldiethylenetriamine, sodium gluconate, sodium tartrate, sodium benzoate, terephthalic acid, and p-toluenesulfonic acid.
[0021] Preferably, the buffer is sodium acetate and / or potassium acetate.
[0022] Preferably, to further improve the uniformity of the alloy distribution and the uniformity of the bright area, the additive further includes a surfactant; the surfactant is one or more of sodium alkyl succinate sulfonate, sodium 2-ethylhexyl sulfonate, and nonionic surfactant EO-PO copolymer; the basic refining agent used in conjunction with the surfactant can produce a synergistic effect and significantly improve the uniformity of the alloy distribution.
[0023] Preferably, the alkyl succinate sodium sulfonate is dioctyl succinate sodium sulfonate, diisooctyl succinate sodium sulfonate, n-butyl succinate sodium sulfonate, or isobutyl succinate sodium sulfonate.
[0024] An acidic zinc-nickel electroplating solution prepared using the above-mentioned acidic zinc-nickel alloy additive has the advantages of low foaming and low main salt content, and includes additives, zinc chloride, and nickel chloride; Zinc chloride provides zinc ions, resulting in a zinc ion concentration of 5-25 g / L in the electroplating solution. Nickel chloride provides nickel ions, with a concentration of 3-20 g / L; The total chloride ion concentration is 80-190 g / L.
[0025] Preferably, the zinc ion concentration is 10-20 g / L, and the nickel ion concentration is 5-15 g / L.
[0026] When using the above-mentioned electroplating solution, control the temperature of the electroplating solution to 30-40℃, and adjust the pH of the electroplating solution to 5.0-6.0 using a 1:1 hydrochloric acid aqueous solution or a dilute potassium hydroxide solution.
[0027] Preferably, during the electroplating process, the electroplating temperature is 33-37℃ and the pH is 5.1-5.6.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: The additive of this invention uses naphthol alkoxy compounds as a basic refining agent for the first time. The electrolyte prepared using this additive can still produce a zinc-nickel plating with fine crystals, normal thickness, and nickel content (10-16%) when the zinc ion concentration is 10-20 g / L and the nickel ion concentration is 5-15 g / L. This effectively reduces production costs and carry-over consumption. In addition, the electroplating solution has less foam and is easy to manage. Attached Figure Description
[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 The iron test piece was polished to a mirror finish with a cloth wheel and then placed in a Hull groove.
[0031] Figure 2 These are photos of the electroplating process. Detailed Implementation
[0032] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.
[0033] The acidic zinc-nickel electroplating bath anode mentioned in this invention uses a zinc anode (99.99% pure zinc) and an electrolytic nickel anode; The acidic zinc-nickel alloy additive of this invention can be used in acidic zinc plating or zinc alloy electroplating solutions, and is particularly suitable for acidic zinc-nickel electroplating solutions (such as our ZNSPIRIT). ® In the 920 acid zinc-nickel alloy electroplating process, the selection range of each component in the electroplating solution is as follows: The zinc ion concentration is 5-25 g / L; Nickel ion concentration is 3-20 g / L; The potassium chloride concentration is 180-250 g / L; The chloride ion concentration is 120-170 g / L; The basic refining agent concentration is 0.5-5 g / L; The concentration of brightener is 0.005-1 g / L; The concentration of the complexing agent is 0.5-5 g / L; The buffer concentration is 40-70 g / L.
[0034] In this invention, 100L of ZNSPIRIT is prepared. ® The process for 920 acidic zinc-nickel alloy electroplating solution is as follows: SS1, add 70L of pure water to the plating tank and heat to 35℃; Add zinc chloride, nickel chloride, and potassium chloride slowly while stirring, and stir until completely dissolved; SS3, Detect the pH value of the plating solution, and slowly adjust the pH value to 5.4±0.1 with analytical grade hydrochloric acid; SS4, add the required amount of ZNSPIRIT sequentially. ® 920D buffer and ZNSPIRIT ® 920C complexing agent, stir well; SS5, add the required amount of ZNSPIRIT sequentially. ® 920A base refining agent and ZNSPIRIT ® 920B brightener, stir well; SS6, add pure water to make up to a working volume of 100L; SS7, check the pH value again, and slowly adjust it with dilute hydrochloric acid or 10% potassium hydroxide solution until the pH value stabilizes at 5.1-5.6; SS8, low current (0.2A / dm) 2 Electrolysis for 6 hours, then trial plating begins.
[0035] The method for synthesizing naphthol alkoxy compounds in this invention is as follows: S1, Naphthol derivative and sodium hydroxide are mixed in a reaction vessel, and high-purity nitrogen is blown into the reaction vessel four times to replace the water. Then, the mixture is dehydrated under a vacuum of -0.1 MPa. Sodium hydroxide accounts for 0.25% of the mass of the naphthol derivative. Continue adding ethylene oxide and stir until homogeneous at 15 rpm; The molar ratio of naphthol derivative to ethylene oxide is 1:10. S2, the pressure inside the reactor is controlled at ≤0.4MPa, the stirring speed is 15 rpm, and the temperature is 105℃, so that the naphthol derivative and ethylene oxide undergo a polymerization reaction for 3.5h to obtain the first block copolymer; S3, propylene oxide is added to the reactor, and the pressure inside the reactor is controlled to be ≤0.4MPa, the stirring speed is 15 rpm, and the temperature is 110℃, so that the first block copolymer and propylene oxide continue to polymerize. The reaction time is 3h, and crude naphthol alkoxy compound is obtained. The molar ratio of naphthol derivative to propylene oxide is 1:5. S4. Neutralizing agent (glacial acetic acid) is added to the crude naphthol alkoxy compound for neutralization, and then adsorbent (activated carbon) is added. After vacuum dehydration and drying, the naphthol alkoxy compound is obtained.
[0036] Example 1 An electroplating solution prepared using a low-foaming, low-primary-salt acidic zinc-nickel alloy electroplating additive includes the following basic refining agent, brightener, complexing agent, buffer, zinc chloride, and nickel chloride; The basic refining agent is an alkoxylated compound of α-naphthol, with R2 being H, EO number 10, PO number 2, and R3 being H; the brightening agent is sodium saccharin; the complexing agent is sodium benzoate; and the buffer is potassium acetate. Among them, zinc chloride 40 g / L, nickel chloride hexahydrate 80 g / L, potassium chloride 200 g / L, potassium acetate 50 g / L, sodium benzoate 1.4 g / L, sodium saccharin 0.4 g / L, and alkoxy compounds of α-naphthol 1.5 g / L; Add 500 ml of the above solution to a Hull cell. Use an electrolytic nickel anode as the anode and a 0.3 mm thick iron sample (6.5 cm × 20 cm) polished to a mirror finish with a cloth wheel as the cathode. Place the Hull cell in a constant temperature water bath, controlling the temperature of the iron sample at 35 °C and the current density at 2 A / dm³. 2 The electroplating time was 10 min. The first point was taken 1 cm from the left edge of the iron sample, and points were taken every 2 cm. The thickness of each point was measured using an X-ray fluorescence thickness gauge. The results are shown in Table 1 below. Table 1 Measurement Results
[0037] Example 2 An electroplating solution prepared using a low-foaming, low-primary-salt acidic zinc-nickel alloy electroplating additive includes the following basic refining agent, brightener, complexing agent, buffer, surfactant, zinc chloride, and nickel chloride; Among them, the basic refining agent is an alkoxy compound of β-naphthol, R1 is NH2, EO number is 5, PO number is 5, and R3 is CH2SO3K; the brightening agent is sodium saccharin, the complexing agents are sodium benzoate and diethylenetriamine, the buffer is sodium acetate, and the surfactant is sodium 2-ethylhexylsulfonate. The composition includes: zinc chloride 40 g / L, nickel chloride hexahydrate 60 g / L, potassium chloride 200 g / L, sodium acetate 60 g / L, sodium benzoate 0.5 g / L, diethylenetriamine 1.0 g / L, sodium saccharin 0.4 g / L, sodium 2-ethylhexylsulfonate 0.5 g / L, and alkoxy compounds of β-naphthol 2.0 g / L. Add 500 ml of the above solution to a Hull cell. Use an electrolytic nickel anode as the anode and a 0.3 mm thick iron sample (6.5 cm × 20 cm) polished to a mirror finish with a cloth wheel as the cathode. Place the Hull cell in a constant temperature water bath, controlling the temperature of the iron sample at 35 °C and the current density at 2 A / dm³. 2 The electroplating time was 10 minutes. The first point was taken 1 cm from the left edge of the iron sample, and points were taken every 2 cm. The thickness of each point was measured using an X-ray fluorescence thickness gauge. The results are shown in Table 2 below. Table 2 Measurement Results
[0038] Example 3 An electroplating solution prepared using a low-foaming, low-primary-salt acidic zinc-nickel alloy electroplating additive includes the following basic refining agent, brightener, complexing agent, buffer, surfactant, zinc chloride, and nickel chloride; The basic refining agent is a β-naphthol alkoxy compound, R1 is H, the number of EOs is 15, the number of POs is 1, and R3 is CH2CH2CH2SO3K; the brightening agent is benzyl acetone, the complexing agents are p-toluenesulfonic acid and diethylenetriamine, the buffer is potassium acetate, and the surfactant is an EO-PO copolymer. The composition includes: zinc chloride 40 g / L, nickel chloride hexahydrate 60 g / L, potassium chloride 220 g / L, potassium acetate 55 g / L, p-toluenesulfonic acid 0.3 g / L, diethylenetriamine 1.0 g / L, benzyl acetone 0.01 g / L, EO-PO copolymer 0.6 g / L, and β-naphthol alkoxy compound 2.0 g / L. Add 500 ml of the above solution to a Hull cell. Use an electrolytic nickel anode as the anode and a 0.3 mm thick iron sample (6.5 cm × 20 cm) polished to a mirror finish with a cloth wheel as the cathode. Place the Hull cell in a constant temperature water bath, controlling the temperature of the iron sample at 35 °C and the current density at 2 A / dm³. 2 The electroplating time was 10 min. The first point was taken 1 cm from the left edge of the iron sample, and points were taken every 2 cm. The thickness of each point was measured using an X-ray fluorescence thickness gauge. The results are shown in Table 3 below. Table 3 Measurement Results
[0039] Example 4 An electroplating solution prepared using a low-foaming, low-primary-salt acidic zinc-nickel alloy electroplating additive includes the following basic refining agent, brightener, complexing agent, buffer, surfactant, zinc chloride, and nickel chloride; Among them, the basic refining agent is an alkoxy compound of α-naphthol, R2 is SO3K, the EO number is 15, the PO number is 8, and R3 is CH2CH2SO3K; the brightening agent is butynediol, the complexing agents are sodium benzoate and triethanolamine, the buffer is sodium acetate, and the surfactant is sodium dioctyl succinate sulfonate. The components are: zinc chloride 30 g / L, nickel chloride hexahydrate 40 g / L, potassium chloride 220 g / L, sodium acetate 65 g / L, sodium benzoate 0.3 g / L, triethanolamine 1.0 g / L, butynediol 0.2 g / L, sodium dioctyl succinate sulfonate 0.5 g / L, and alkoxy compounds of α-naphthol 2.5 g / L. Add 500 ml of the above solution to a Hull cell. Use an electrolytic nickel anode as the anode and a 0.3 mm thick iron sample (6.5 cm × 20 cm) polished to a mirror finish with a cloth wheel as the cathode. Place the Hull cell in a constant temperature water bath, controlling the temperature of the iron sample at 35 °C and the current density at 2 A / dm³. 2 The electroplating time was 10 minutes. The first point was taken 1 cm from the left edge of the iron sample, and points were taken every 2 cm. The thickness of each point was measured using an X-ray fluorescence thickness gauge. The results are shown in Table 4 below. Table 4 Measurement Results
[0040] Example 5 An electroplating solution prepared using a low-foaming, low-primary-salt acidic zinc-nickel alloy electroplating additive includes the following basic refining agent, brightener, complexing agent, buffer, surfactant, zinc chloride, and nickel chloride; Among them, the basic refining agent is β-naphthol alkoxy compound, R1 is Cl, EO number is 3, PO number is 5, and R3 is H; the brightening agent is butynediol monooxy compound, the complexing agent is tetraethylenepentamine and sodium tartrate, the buffer is potassium acetate, and the surfactant is sodium isobutylsuccinate sulfonate. The following components are present: zinc chloride 30 g / L, nickel chloride hexahydrate 30 g / L, potassium chloride 240 g / L, potassium acetate 50 g / L, tetraethylenepentamine 0.3 g / L, sodium tartrate 1.0 g / L, butynediol monooxygenate 0.2 g / L, sodium isobutylsuccinate sulfonate 1.0 g / L, and β-naphthol alkoxygenate 1.5 g / L. Add 500 ml of the above solution to a Hull cell. Use an electrolytic nickel anode as the anode and a 0.3 mm thick iron sample (6.5 cm × 20 cm) polished to a mirror finish with a cloth wheel as the cathode. Place the Hull cell in a constant temperature water bath, controlling the temperature of the iron sample at 35 °C and the current density at 2 A / dm³. 2 The electroplating time was 10 minutes. The first point was taken 1 cm from the left edge of the iron sample, and points were taken every 2 cm. The thickness of each point was measured using an X-ray fluorescence thickness gauge. The results are shown in Table 5 below. Table 5. Measurement Results
[0041] Example 6 An electroplating solution prepared using a low-foaming, low-primary-salt acidic zinc-nickel alloy electroplating additive includes the following basic refining agent, brightener, complexing agent, buffer, surfactant, zinc chloride, and nickel chloride; Among them, the basic refining agent is an alkoxy compound of β-naphthol, R1 is COCH3, EO number is 3, PO number is 3, and R3 is CH2SO3K; the brightening agent is benzyl acetone and sodium vinyl sulfonate, the complexing agent is terephthalic acid and sodium gluconate, the buffer is potassium acetate, and the surfactant is sodium isobutylsuccinate sulfonate. The composition includes zinc chloride 30 g / L, nickel chloride hexahydrate 40 g / L, potassium chloride 230 g / L, potassium acetate 45 g / L, terephthalic acid 0.8 g / L, sodium gluconate 0.5 g / L, benzyl acetone 0.01 g / L, sodium vinyl sulfonate 0.2 g / L, and alkoxy compounds of β-naphthol 3.0 g / L. Add 500 ml of the above solution to a Hull cell. Use an electrolytic nickel anode as the anode and a 0.3 mm thick iron sample (6.5 cm × 20 cm) polished to a mirror finish with a cloth wheel as the cathode. Place the Hull cell in a constant temperature water bath, controlling the temperature of the iron sample at 35 °C and the current density at 2 A / dm³. 2 The electroplating time was 10 minutes. The first point was taken 1 cm from the left edge of the iron sample, and points were taken every 2 cm. The thickness of each point was measured using an X-ray fluorescence thickness gauge. The results are shown in Table 6 below. Table 6 Measurement Results
[0042] A comparison of the overall performance after electroplating in Examples 1-6 is shown in Table 7 below: Table 7 Performance Comparison Results
[0043] As can be seen from Table 7, Example 3 has excellent performance in all aspects, with very good coating brightness, good dispersion, and nickel content in the coating that is basically within the normal range and relatively uniformly distributed. Although the coating in Example 6 has excellent brightness, its dispersibility is poor and the nickel content is unevenly distributed. Example 2: The coating brightness and dispersion are average. The nickel content of the coating is slightly uniform, but slightly higher at the later points. Example 1: The coating has good brightness, moderate dispersion, and slightly uniform nickel content, but slightly higher at the later points. Example 5: The coating has moderate brightness, good dispersion, and moderate nickel content distribution. Example 4 shows that the coating has good brightness, moderate dispersion, and moderate nickel content distribution.
[0044] Although the present invention has been described in detail with reference to preferred embodiments, it is not limited thereto. Various equivalent modifications or substitutions can be made to the embodiments of the present invention by those skilled in the art without departing from the spirit and essence of the invention, and such modifications or substitutions should all be within the scope of the present invention. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should also be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention should be determined by the scope of the claims.
Claims
1. An acidic zinc-nickel alloy additive, characterized in that, It includes a basic refining agent of 0.5-5 g / L, a brightening agent of 0.005-1 g / L, a complexing agent of 0.5-5 g / L, and a buffer of 40-70 g / L; The basic refining agent is a naphthol alkoxy compound with a structure as shown in Formula I or Formula II, as follows: (I) (II) Among them, R1 is one of H, Cl, Br, NH2, and COCH3; R2 is one of H, F, Cl, Br, NH2, SO3K, or COCH3; R3 is one of H, CH2SO3K, CH2CH2SO3K, and CH2CH2CH2SO3K.
2. The acidic zinc-nickel alloy additive as described in claim 1, characterized in that, When the naphthol alkoxy compound is an alkoxy compound of α-naphthol, such as in Formula II, R2 is any one of H, F, Cl, Br, NH2, SO3K, and COCH3, and R3 is any one of H, CH2SO3K, CH2CH2SO3K, and CH2CH2CH2SO3K. When the naphthol alkoxy compound is an alkoxy compound of β-naphthol, as in Formula I, R1 is any one of H, Cl, Br, NH2, and COCH3, and R3 is any one of H, CH2SO3K, CH2CH2SO3K, and CH2CH2CH2SO3K. The number of poly(ethylene oxide) blocks in the naphthol alkoxy compound is m, and the number of poly(propylene oxide) blocks is n, wherein 1≤m≤20, 1≤n≤15, and preferably, 1≤m≤15, 1≤n≤10.
3. The acidic zinc-nickel alloy additive as described in claim 1, characterized in that, A method for synthesizing naphthol alkoxy compounds, comprising: polymerizing a naphthol derivative with ethylene oxide to obtain a first block copolymer; The molar ratio of naphthol derivatives to ethylene oxide is 1:0.5-20; The first block copolymer is then further polymerized with propylene oxide to obtain the naphthol alkoxy compound; The molar ratio of naphthol derivatives to propylene oxide is 1:0.5-12.
4. The acidic zinc-nickel alloy additive as described in claim 3, characterized in that, The molar ratio of the naphthol derivative to ethylene oxide is 1:1-15; The molar ratio of the naphthol derivative to propylene oxide is 1:1-8.
5. The acidic zinc-nickel alloy additive as described in claim 4, characterized in that, The specific methods for synthesizing naphthol alkoxy compounds are as follows: S1, place the naphthol derivative and the base in a reaction vessel and mix them. Purge the reaction vessel with nitrogen, evacuate it, and then dehydrate it under vacuum. Continue to add ethylene oxide and stir until homogeneous at 14-17 rpm. S2, control the pressure inside the reactor to ≤0.4MPa, the stirring speed to 14-17 rpm, and the temperature to 100-120℃, so that the naphthol derivative and ethylene oxide can undergo a polymerization reaction for 1-5 hours to obtain the first block copolymer; S3, add propylene oxide into the reactor, control the pressure inside the reactor to ≤0.4MPa, the stirring speed to 14-17 rpm, and the temperature to 100-120℃, so that the first block copolymer and propylene oxide continue to polymerize. The reaction time is 1-5h, and crude naphthol alkoxy compound is obtained. S4. Neutralize the crude naphthol alkoxy compound by adding a neutralizing agent, then add an adsorbent, and obtain the naphthol alkoxy compound after vacuum dehydration and drying.
6. The acidic zinc-nickel alloy additive as described in claim 5, characterized in that, In step S1, the base is 0.20-0.30% of the mass of the naphthol derivative; the base is sodium hydroxide and / or potassium hydroxide; the gas is purged with high-purity nitrogen four times; the vacuum degree is -0.1 MPa during evacuation.
7. The acidic zinc-nickel alloy additive as described in claim 1, characterized in that, The brightening agent is one or more of benzyl acetone, butynediol, butynediol monooxy compound, sodium vinyl sulfonate, and sodium saccharin. The complexing agent is any one or a combination of diethylenetriamine, hydroxyethyldiethylenetriamine, tetraethylenepentamine, triethanolamine, N,N-tetramethylethylenediamine, 1,1,4,7,10,10-hexamethyltriethylenetetramine, pentamethyldiethylenetriamine, sodium gluconate, sodium tartrate, sodium benzoate, terephthalic acid, and p-toluenesulfonic acid. The buffer is sodium acetate and / or potassium acetate; The additive also includes a surfactant; the surfactant is one or more of sodium alkyl succinate sulfonate, sodium 2-ethylhexyl sulfonate, and nonionic surfactant EO-PO copolymer.
8. The acidic zinc-nickel alloy additive as described in claim 7, characterized in that, The alkyl succinate sodium sulfonate is sodium dioctyl succinate sodium sulfonate, sodium diisooctyl succinate sodium sulfonate, sodium n-butyl succinate sodium sulfonate, or sodium isobutyl succinate sodium sulfonate.
9. An acidic zinc-nickel electroplating solution prepared using the acidic zinc-nickel alloy additive as described in claim 1, characterized in that, Including additives, zinc chloride, and nickel chloride; Zinc chloride provides zinc ions, resulting in a zinc ion concentration of 5-25 g / L in the electroplating solution. Nickel chloride provides nickel ions, with a concentration of 3-20 g / L; The total chloride ion concentration is 80-190 g / L.
10. The acidic zinc-nickel electroplating solution as described in claim 9, characterized in that, When using, control the temperature of the electroplating solution to 30-40℃, and adjust the pH of the electroplating solution to 5.0-6.0 using a 1:1 hydrochloric acid aqueous solution or a dilute potassium hydroxide solution; preferably, during the electroplating process, the electroplating temperature is 33-37℃ and the pH is 5.1-5.6.